(untitled) - Richards, Michael D. (London/New York, 2004)
Revolutions have been a part of politics for centuries. Their ideologies, their leaders, and their successes or failures have shaped the history of nations worldwide. This broad comparative survey focuses on five big case studies, starting with the English Revolutions in the Seventeenth century, and going on to the Mexican, Russian, Vietnamese and Iranian Revolutions. Revolutions in World Historytraces the origins, developments, and outcomes of these revolutions, providing an understanding of the revolutionary tradition in a global context. Questions about motivations and ideologies are raised as well as about the effectiveness of these revolutions - and revolution as a concept - in bringing about lasting political changes
Keywords: Revolutions,Revolutions; History,Case studies